Optimisation of broilers performance to different dietary levels of fibre and different levels and sources of fat from 0 to 14 days of age. Issue 1 (1st January 2021) - Aziz-Aliabadi, Fatemeh; Hassanabadi, Ahmad; Golian, Abolghasem; Zerehdaran, Saeed
Abstract: Central composite design (CCD; 3 levels and 3 factors) and response surface methodology (RSM) were used to evaluate the average daily body weight gain (ADG) and feed conversion ratio (FCR) in broiler chicks to different levels of dietary sugar beet pulp (SBP), tallow (T) and soybean oil (SO). A total of 60 battery brooder cages of 7 birds each were assigned to 15 diets of CCD containing 3 levels of SBP (0.00, 1.75, 3.50%), T (0.00, 0.50, 1.00%) and SO (0.00, 0.50, 1.00%), from 0 to 14 days of age. The testable outcomes of CCD were fitted with the quadratic model. The response surface analysis showed significant linear, quadratic, and interaction models for ADG and FCR from 0 to 7 and 7 to 14 days of age. At 7 days of age, maximum ADG and minimum FCR were observed with 0.00% of SBP, T, and SO in the diet. At 14 days of age, maximum ADG was obtained at 0.60%, 0.33% and 0.45% of SBP, T and SO in the diet, and the minimum FCR was observed with 0.98%, 0.00% and 1.00% of SBP, T and SO in diet, respectively. The results of this study showed that with increasing age and development of the gastrointestinal tract of broilers, adverse effects of soluble fibres are reduced, and response surface models can explain the correlation among dietary nutrient concentrations and young broiler performance to achieve the optimal target. HIGHLIGHTS: Central composite design reduces the number of trials and the costs. The development of the gastrointestinal tract will moderate the adverse effects of dietary soluble fibre. By the response surface model, the correlations between dietary nutrients can be explained.